The Role of Villages in Increasing Awareness of Land Administration Order in Jayanegara Village - Dewi, Sartika; Hardiansyah, Dicky; Mahfud, Fuad; Casmita, Kusnadi; Latif, Muhammad; Sadam M, Mochammad Reyza; Alghifari, Zakaria Restu (PT. Hafasy Dwi Nawasena, 2024)
The Village Government is the smallest government in Indonesia with the task of protecting every element of the community who resides in the village, this is in accordance with the mandate of Article 26 Paragraph 1 of Law Number 6 of 2014 which is explained that the Village Head also empowers and coaches the community. Thus, the role of the village government in improving the order of population administration and civil registration is very important. One of the administrative orders carried out by Jayanegara village is administrative order in the field of land, with the existence of the Complete Systematic Land Registration (PTSL) program organized by the government with the aim of preventing land disputes in the community, this PTSL program is an activity whose scope includes activities to register land whose implementation is carried out en masse or simultaneously for all land registrants, especially in village area, including collecting and determining the correctness of land registration documents. The objectives of this study include: to find out the role of villages in increasing awareness of land administration order and supporting factors in improving land administration order. Qualitative research method with an empirical juridical approach. The results of this study show that the role of villages in the order of land administration in Jayanegara Village is quite good, with the PTSL program which targets as many as 126 million land plots to be given land rights certificates, in 2022 as many as 102.3 million land plots that have received certificates, the certificate target for 126 million land plots can be realized in 2025. Jayanegara Village achieved land certification with a total of 1,200 land plots, this provides an increase in the number of land that already has certificates. In the implementation of services, supporting factors in improving the order of land administration of the PTSL program include: a good and conducive work environment, the discipline of PTSL officers in completing the PTSL process, the motivation and supervision carried out by the village head.